The mythical creatures bible : the definitive guide to legendary beings - Rosen, Brenda (New York : Sterling, 2009)
Mythical creatures that come from the land, sea, air, and beyond your wildest imagination...--P. [4] of cover.
Includes index.
Keywords: Animals, Mythical -- Encyclopedias